Profile: Understanding the 2022-23 Peruvian Uprising - Disi-Pavlic, R (Routledge, 2025)
This profile examines Peru’s unexpected popular uprising of 2022–23, which is distinct from its neighbors due to decades of relative calm. We combine three concepts emphasizing time-varying processes: deep-rooted societal inequality across class, ethnicity, and regions resulting in a fragmented civil society (long term); a mounting crisis in political representation (medium term); and the immediate trigger, namely, the removal of President Pedro Castillo (short term), which incited his supporters and sparked widespread protests. © 2024 Informa UK Limited, trading as Taylor & Francis Group.